2016
DOI: 10.1080/13880209.2016.1235208
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of biological activity of Mentha species extracts on apoptotic and autophagic targets on murine RAW264.7 and human U937 monocytic cells

Abstract: Context: Mints (Lamiaceae) are used as traditional remedies for the treatment of several diseases. Their extracts are recognized as anti-inflammatory compounds.Objective: This study characterized the cytotoxic effects of Mentha spicata L. (MS), Mentha pulegium L. (MP) and Mentha rotundifolia (L). Huds (MR) on macrophage cells (RAW264.7; U937) and determined their impact on apoptosis and autophagy, which can play a role in controlling inflammation.Materials and methods: The extracts were prepared in culture med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…It is important to emphasize that the use of 7KC (25–50 µM) on different cell types is a relevant model: (a) to evaluate the relationship between oxidative stress, apoptosis and autophagy; (b) to specify the part played by the organelles (mitochondria, peroxisomes and lysosomes) in these processes; (c) to determine the interactions between these organelles, and (d) to identify natural and synthetic molecules able to prevent 7KC-induced side effects [22]. In addition, mint extracts were used in a range of non-toxic concentrations: (25 to 400 µg/mL) to study their effects on cell death, and (200 and 400 µg/mL) to determine their impact on cytokine secretion [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to emphasize that the use of 7KC (25–50 µM) on different cell types is a relevant model: (a) to evaluate the relationship between oxidative stress, apoptosis and autophagy; (b) to specify the part played by the organelles (mitochondria, peroxisomes and lysosomes) in these processes; (c) to determine the interactions between these organelles, and (d) to identify natural and synthetic molecules able to prevent 7KC-induced side effects [22]. In addition, mint extracts were used in a range of non-toxic concentrations: (25 to 400 µg/mL) to study their effects on cell death, and (200 and 400 µg/mL) to determine their impact on cytokine secretion [30].…”
Section: Discussionmentioning
confidence: 99%
“…Among these phytochemicals, phenolic compounds and carotenoids include many different families of aromatic secondary metabolites in plants. Interestingly, mint extracts at their bioactive dilutions had no observable toxicity in our previous study [30].…”
Section: Introductionmentioning
confidence: 92%
“…The genus of Mentha have also been shown to have many biological activities, and especially anti-tumoral activity. Many studies have demonstrated the effect of Mentha species EOs as inhibiting the cell proliferation of numerous tumor cells by acting on mitochondrial dysfunctions, apoptosis induction, and autophagy processes [84].…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…Despite that the genus Mentha has been largely studied for both essential oil and phenolic content, chemical characterization of polyphenols from M. rotundifolia has been documented in very few reports but never from Tunisian populations [17,18]. In view of exploring the chemistry and the bioactivity potential of M. rotundifolia from Tunisia, we carried out a collection of plant samples from different sites.…”
Section: Resultsmentioning
confidence: 99%